High congruence of intraspecific variability in floral scent and genetic patterns in Gentianella bohemica Skalický (Gentianaceae). (April 2017) - Schiebold, Julienne Marie-Isabelle; Feulner, Martin; Dötterl, Stefan; Lauerer, Marianne
Abstract: Gentianella bohemica Skalický (Gentianaceae) is a critically endangered species endemic to the Bohemian Massif in the border region of Germany, Czechia and Austria. It consists of a restricted number of extremely scattered populations which are known to form distinct genetic groups. The objective of this work was to test for differences in the floral scent between Gentianella bohemica and Gentianella germanica and within these two species among populations, and to test for a correlation of scent and genetic similarity among the populations of G. bohemica . Floral scent was collected from the inflorescences/plants of eight flowering populations of G. bohemica and three populations of G. germanica using dynamic headspace methods, followed by GC/MS analyses. Both species emitted several aromatic and terpenoid compounds and multivariate analyses revealed differences in scent between the two species and within species among G. bohemica populations. Volatile components overlapped as expected for closely related species but floral scent was taxon-specific. Floral scent differentiation among G. bohemica populations was in high congruence with the genetic differentiation suggesting that scent differences among populations have a genetic basis and showing that scent is a suitable chemotaxonomic marker in this species. Highlights: Gentianella bohemica is a critically endangered species endemic to the Bohemian Massif. G. bohemica consists of scattered populations forming distinct genetic groups. Floral scent was taxon-specific for G. bohemica and G. germanica. Floral scent differentiation among G. bohemica populations highly correlated with AFLP data. Floral scent is a suitable chemotaxonomic marker in G. bohemica.